Hi! I'm having trouble with this problem... I've been staring at it for a couple days now, and still can't figure it out...

"Using the forward difference operator $\displaystyle \bigtriangleup P(x) = P(x+1)-P(x)$,

$\displaystyle f[x_{0},x_{1}]=\frac{f(x_{1})-f(x_{0})}{x_{1}-x_{0}}=\frac{1}{h}\bigtriangleup f(x_{0})$
$\displaystyle f[x_{0},x_{1},...,x_{k}]=\frac{1}{k!h^{k}}\bigtriangleup ^{k}f(x_{0})$

we have:

$\displaystyle P_{n}(x_{0}+sh)=f[x_{0}]+ \sum_{k=1}^{n}\binom{s}{k}\bigtriangleup ^{k}f(x_{0})$

A fourth degree polynomial P(x) satisfies:
$\displaystyle \bigtriangleup ^{4}P(0)=24$
$\displaystyle \bigtriangleup ^{3}P(0)=6$
$\displaystyle \bigtriangleup ^{2}P(0)=0$

Compute $\displaystyle \bigtriangleup ^{2}P(10)$"

I'm not even sure how to approach this problem... Help!